Urban struggles with financialization. Issue 11 (8th September 2017) - Fields, Desiree
Abstract: The 2008 financial crisis and its impacts on the urban landscape contributed to a proliferation of research on the financialization of urban space, particularly of housing. Today, financialization is a mainstream focus of study within geography. But while scholars have responded to earlier calls to center space and place in their research, it has only been quite recently that geographers have taken up efforts to politicize and contest the financialization of urban space. This essay assesses the emerging body of literature on urban struggles with financialization. It first draws on historical materialist perspectives to situate financialization within urban contexts, showing why there is a particular relationship between this process and urban space, and how moments of crisis reveal tensions in this relationship. Reviewing literature focused on places exposed to the most systemic housing–financial crises in 2008, the essay then explores how residents, activists, and movements have grappled with financialization. It argues that a key aspect of such struggles is the ability to make their presence felt within chains of financial intermediaries or the corporate headquarters of foreign investors. The essay also highlights how moments of crisis open space for more radical tactics that disrupt the dominant production of space and emphasize the social value of housing. It suggests ways to fruitfully expand geographic inquiry into urban struggles with financialization through focusing on the formation of political subjectivities and engaging geographies beyond the global north.